Investigation of temperature influence on the process of reduction of graphene oxide - Kuanyshbekov, T.K.; Tulegenova, М.А.; Baigarinova, G.A.; Guseinov, N.R.; Ilyin, A.M. (Recent Contributions to Physics, 2017)
The paper presents the results of influence different temperature on reducing graphene oxide. The influence of atmosphere pressure hydrogen gas at temperatures: 150 °C, 300 °C, 500 °C, 900 °C on the structure and composition of functionalized graphene was studied. The positions and ratio of Raman peaks of graphene oxide and thermally-reduced graphene are shown. Collected SEM images of graphene oxide are demonstrates layered structure, and the elemental composition of the thermally-reduced graphene at various temperatures was determined by using EDX spectroscopy. The obtained elemental analysis results are in good agreement with the data on the mass loss of thermally-reduced graphene, which is explained by the removal of functional groups.